Predictive Validity of Interviewer Post-interview Notes on Candidates’ Job Outcomes: Evidence Using Text Data From a Leading Chinese IT Company - Liu, Shanshi; Chang, Yuanzheng; Jiang, Jianwu; Ma, Haigang; Zhou, Huaikang (Frontiers in Psychology, 2021)
Despite the popularity of the employment interview in the employee selection literature and organizational talent selection process, few have examined the comments interviewers give after each interview. This study investigated the predictability of the match between interviewer narrative comments and job analysis on the candidate’s later career performance using text mining techniques and data from one of the largest internet-based technology companies in China. A large sample of 7650 interview candidates who passed the interviews and joined the company was obtained to show that the number of job-related capabilities interviewers mentioned in their comments was positively related to candidate’s job performance, the number of promotions, and negatively related to turnover. Moreover, the dimensions of the job analysis covered in the interview moderated the predictability of interview narrative comments. Our results indicated that a smaller number of job analysis dimensions by which interviewers assessed the candidates in the interview positively moderated candidates’ promotion for product development jobs, and negatively moderated turnover for technical jobs. The implications of these results for structured interview research in both theory and practice are discussed.